An accelerometer-based system for elite athlete swimming performance analysis - Davey, N. P.; Anderson, M. E.; James, D. A. (Proceedings of SPIE, 2005)
The measurement of sport specific performance characteristics is an important part of an athletes training and preparation for competition. Thus automated measurement, extraction and analysis of performance measures is desired and addressed in this paper. A tri-axial accelerometer based system was located on the lower back or swimmers to record acceleration profiles. The accelerometer system contained two ADXL202 bi-axial accelerometers positioned perpendicular to one another, and can store over 6 hours of data at 150Hz per channel using internal flash memory. The simultaneous collection of video and electronics touch pad timing was used to validate the algorithm results. Using the tri-axial accelerometer data, algorithms have been developed to derive lap times and stroke count. Comparison against electronic touch pad timing against accelerometer lap times has produced results with a typical error of better than ±0.5 seconds. Video comparison of the stroke count algorithm for freestyle also produced results with an average error of ±1 stroke. The developed algorithms have a higher level of reliability compared to hand timed and counted date that is commonly used during training.